Modeling frequency response of transformer winding to investigate the influence of RLC - S Al-Ameri; M. F. M. Yousof; Norhafiz Azis; S. Avinash; M. A. Talib; Ali. A. Salem (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Frequency response measurements are used for power transformer winding failures detection. The variation between frequency responses indicate mechanical changes in the transformer winding. One method to investigate winding failures in transformer is to develop a reliable circuit model which can simulate the frequency response of an actual winding. The main reason to use the model is because it is expensive to create damages on an actual winding. This paper proposes n-stages circuit ladder network to simulate the response of a winding which has unique design. It presents a new technique to calculate the resistance, inductance and capacitance of the winding. Then, the relationship between the RLC parameters and the frequency response is studied. The winding chosen in this investigation is a single phase 33kV transformer winding. The simulated frequency response was compared with the measured response to verify the proposed model. The model can give a comprehensive understanding about the effect of RLC parameters on the frequency response.